Outcomes of Endoscopic Management of Symptomatic Pancreatic Duct Stones - Azar, Riad R. (2012)
Obstruction of the main pancreatic duct (PD) by stones (PDS) can cause significant pain in patients with chronic pancreatitis (CP). Endoscopic therapy (ET) is an option for patients with symptomatic PDS, however, predictors of successful endoscopic removal of PDS have not been well defined.